Padrões de desfolha do milheto pastejado por bezerras de corte - Monfardini, Liana (2021)
The work was carried out aiming to evaluate intensity, frequency of defoliation and millet (Pennisetum americanum (L.) Leeke) characteristics grazed by beef heifers in two phenological stages. The continuous stocking rate grazing method was used with a variable number of animals to keep the canopy height between 30 and 40 cm. The experimental design used was completely randomized with two phenological stages (vegetative and pre-reproductive) with eight replications of area. The total number of leaves was 21.8% higher in vegetative stage, while population density of basal (116.0 tillers/m²) and axillary tillers (101.4 tillers/m²) were similar phenological stages. Average of defoliation intensity was 47,0% and general defoliation frequency was 0,51 defoliation/tillers/day. Each heifer grazed an area of 395.3 m²/day. Leaf blades were grazed 4.7 times before entering in senescence and the termical accumulation observed between defoliation intervals was sufficient for 1.2 new leaves to be emitted before next defoliation event. Intensity and frequency of defoliation of expanded and expanding leaves were similar, showing that the heifers maintained grazing strategy during analyzed stages.